Presentation meeting on the PES Day tree planting drive by the IEEE UiTM student branch - UiTM, UGC (UiTM Green Centre, 2025)
On 26 March 2025, a presentation meeting for the PES Day project: tree planting drive was conducted by the IEEE UiTM student branch, College of Engineering Studies, UiTM Shah Alam, at the main meeting room, development department.